The Effect of Executive and Ownership Structure on Diversification Behavior: A Research about Businesses Listed In Istanbul Stock Exchange - YİĞİT, İHSAN (ELSEVIER SCIENCE BV, 2012)
There are studies in developed countries about the influence of ownership percentage in board of management on diversification strategy preferences. It is concluded that there is a negative relation between diversification strategy behavior and the ownership percentage of management or other elements of management structure in most of these studies. In this study, it is aimed to test whether there is a relation between executive structure and diversification strategy preferences in our country in light of the means of evidence of agency theory. Herfindahl Index used widely in the literature was used for diversification measure in the study. The data of businesses listed in Istanbul Stock Exchange was used to understand the relation between diversification behavior and executive structure. The data of these businesses were obtained from www.kap.gov.tr and www.imkb.gov.tr.
Keywords: Diversification strategies; diversification degree; ownership structure; agency theory; stewardship theory; Herfindahl index; CORPORATE DIVERSIFICATION; EQUITY OWNERSHIP; AGENCY THEORY